Innovations in the treatment of cervical spine myelopathy – a comprehensive review - Kozikowska, Marta; Pociecha, Agnieszka; Kmak, Bożena (Journal of Education, Health and Sport, 2024)
Introduction and aim of the study Myelopathy of the cervical spine is a set of symptoms resulting from compression of the spinal cord. There are many causes that may lead to this disorder, including degenerative changes, ligament ossification and tumors. Middle-aged and older patients usually suffer from it, and its diagnosis is expected to increase as the population gets older. Due to non-specific and initially mild symptoms, cervical myelopathy is usually diagnosed in later stages, often when the patient's fitness and independence are significantly impaired. The aim of the study is to present the current state of knowledge about myelopathy of the cervical spine, methods of its effective diagnosis, and to present available therapeutic options, because early diagnosis and optimal treatment enable patients to maintain their ability to work and improve their overall quality of life. Materials and methods The literature included in the PubMed, BioMed Central and Polish Medical Platform databases is searched by means of the words such as cervical myelopathy, decompression, spinal cord, corpectomy, discectomy. Quoted sources in selected works were also used. Conclusion Surgical treatment is the most effective method to improve the clinical condition of people suffering from cervical myelopathy. Both anterior and posterior approach surgeries are characterized by similar effectiveness, and the choice of a specific method depends on the patient's general condition, the degree of cervical lordosis, and the number of affected spinal segments. Due to the correct diagnosis of the disease and applying treatment, it is possible to slow down the progression of the disease and improve the quality of life of patients.